2001
DOI: 10.1046/j.1439-0523.2001.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of a gene for leaf scald resistance in barley line ‘B87/14’ and validation of microsatellite and RFLP markers for marker‐assisted selection

Abstract: Seedlings of the barley line ‘B87/14’ were resistant to 22 out of 23 Australian isolates of Rhynchosporium secalis, the causal agent of leaf scald.‘B87/14’‐based populations were developed to determine the location of the resistance locus. Scald resistance segregated as a single dominant trait in BC1F2 and BC1F3 populations. Bulked segregant analysis identified amplified fragment length polymorphisms (AFLPs) with close linkage to the resistance locus. Fully mapped populations not segregating for scald resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Rhynchosporium secalis is a highly variable fungus which is able to overcome single resistance genes quickly (Williams et al 2001). Therefore, it is generally not considered worthwhile to base breeding programmes for Rhynchosporium resistance on single major genes (Jørgensen et al 1995;Tekauz 1991;Salamati and Tronsmo 1997).…”
Section: Diagnostic Molecular Markersmentioning
confidence: 99%
“…Rhynchosporium secalis is a highly variable fungus which is able to overcome single resistance genes quickly (Williams et al 2001). Therefore, it is generally not considered worthwhile to base breeding programmes for Rhynchosporium resistance on single major genes (Jørgensen et al 1995;Tekauz 1991;Salamati and Tronsmo 1997).…”
Section: Diagnostic Molecular Markersmentioning
confidence: 99%
“…These markers may then be used to increase the efficiency of selective breeding programmes by an order of magnitude compared to traditional breeding programmes (Jones et al 2002), something already achieved with resistant crop plants produced using this type of marker-assisted selection (e.g. Williams et al 2001).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…These markers may then be used to increase the efficiency of selective breeding programmes by an order of magnitude compared to traditional breeding programmes (Jones et al 2002), something already achieved with resistant crop plants produced using this type of marker-assisted selection (e.g. Williams et al 2001).In this study the underlying genetic basis for individual and population level differences in resistance was examined using 'Quantitative trait loci' (QTL) analysis. Linkage maps were used to systematically search for chromosomal regions with significant statistical associations with parasite resistance, within salmon families created using hybrid male parents produced from stocks divergent in their ability to resist Gyrodactylus salaris.…”
mentioning
confidence: 99%
“…It has been demonstrated that SSR markers possess a number of advantages over other types of molecular markers, such as codominance, highly polymorphisms, locus specificity, good reproducibility, and random distribution throughout the genome. In recent years, a large number of SSR markers in barley have been developed and extensively utilized in barley genomic mapping and markerassisted breeding (Liu et al 1996;Ramsay et al 2000;Varshney et al 2007;Williams et al 2008).…”
Section: Introductionmentioning
confidence: 99%